(untitled) (Research, Society and Development, 2020)
This work aimed to evaluate the microbiological quality of cow pea (Vigna unguiculata) when subjected to different levels of water replacement due to crop evapotranspiration (ETc) with three concentrations of treated domestic effluent. The plants were grown in pots arranged in a Randomized Block Design (DBC) in a 3 x 4 factorial scheme. The culture was subjected to four levels of water replacement (75, 100, 125 and 150% of ETc) with three concentrations of domestic effluent treated (0, 50 and 100%), with four repetitions. Urban supply water was used for the concentration corresponding to 0%, while in concentrations of 50 and 100%, the effluent was collected from the SewageTreatment Station of the Federal University of Sergipe. Fecal coliforms (NMP g-1) and Salmonella sp. were evaluated. The results of the samples were submitted to analysis according to the parameters recommended by Resolution Nº 12 of 01/02/2001 of the National Health Surveillance Agency - ANVISA. The results showed the absence of Samonella, as well as of microorganisms indicating faecal contamination in the caupi beans, regardless of the treatment used.